Exploring the Perceptions and Challenges of Teenage Pregnancy and Motherhood with Its Way Forward: A Phenomenological Study among the Tribal Population in a Rural Area of Udaipur, Rajasthan, India - Meena Sharma; Raktim Engti; Deepak Mittal (Journal of Primary Care Specialties, 2024)
Background: Teenage pregnancy and motherhood are one of the global public health problems. In India, 6.8% of women aged 15–19 years began childbearing between 2019 and 2021 and this is more common in rural areas and socioeconomically disadvantaged states. During the National Family Health Survey-5, it was seen that 4.2% of 15–19 years were already pregnant or had children. Thus, this study aims to explore the various challenges faced by teenage mothers with the barriers in service delivery and solutions to tackling the issue from their perspective. Materials and Methods: A qualitative study with a phenomenological approach was conducted from October to November’ 2023 in the tribal hamlets of Udaipur, Rajasthan. In-depth interviews of 21 purposively selected with snowball sampling teenage mothers were conducted. Audio recording and note-taking were done during the interview. Thematic analysis was done. Results: The teenage mothers were subjected to various types of medical problems, lack of unawareness, lack of parental and spousal support, as well as psychosocial stressors and social constraints as the major challenges being faced. The major themes for its solutions were parental and spousal cooperation, education, and ownership taken by the village head. Conclusion: Lack of unawareness, medical problems, and familial issues probably due to socioeconomic factors are the major challenges for teenage mothers, whereas the prime solution, as suggested, is parental support and cooperation. Regulation on the sale of alcohol was also cited as a factor in curbing the problems of teenage pregnancy.